Verses on Vehicles: Religion, Romance, and Ritual in Truck Art of Nepal - Sheikh Saifullah Ahmed; Ramesh Prasad Adhikary (Asiatic: IIUM Journal of English Language and Literature, 2026)
This study examines the cultural significance of verses and paintings on long-haul trucks in Nepal. It analyses their articulation of religion, romance, ritual, and their emotional and social resonance for drivers and communities, while situating them within South Asian and global discourses on mobility, material religion, and vernacular culture. Using a mixed-methods approach, fieldwork was conducted at Dhankhola, Dang district of Nepal, with purposive sampling of 135 trucks. Data collection included 90 hours of observation, over 500 photographs, and interviews with 30 drivers, five painters, and two cultural experts. Qualitative data were analysed through content analysis, thematic coding, and visual semiotics, while quantitative analysis quantified the prevalence of different motifs. Findings show religious motifs (58.5%) act as protective talismans, transforming trucks into mobile shrines on dangerous routes. Romantic inscriptions (31.1%) serve as emotional anchors, easing isolation but often reinforcing patriarchal norms. Ritual blessings (27.4%) sustain family ties, satirical commentary (11.1%) channels dissent, and national imagery (16.3%) fosters collective identity. These motifs, grounded in mobilities, material religion, and vernacular frameworks, position trucks as dynamic cultural infrastructure. This research contributes unique insights into South Asian cultural studies by documenting the understudied vehicular art of Nepal and urges to preserve it against the threat of modernisation.